Adverse food reactions: Pathogenesis, clinical signs, diagnosis and alternatives to elimination diets. (June 2018) - Mueller, R.S.; Unterer, S.
Highlights: Adverse food reaction (AFR) is a frequent differential diagnosis for dogs and cats with skin and gastrointestinal disease. Feeding a protein and a carbohydrate previously not fed is needed to diagnose AFR in dogs and cats. Home-cooked as well as commercial hydrolysed diets are recommended. Laboratory tests for adverse food reaction are not helpful for diagnosis of AFR. Avoidance of offending allergens is the optimal treatment for AFR. Abstract: This review summarises available information about adverse food reactions in dogs and cats. Much of the published information on the pathogenesis of adverse food reactions in these species is transferred from what is known in mice and human beings. Clinical signs affect mostly the integument and gastrointestinal system. Pruritus of the distal limbs, face, ears and ventrum is the most common cutaneous presentation in dogs, although urticaria has also been reported. In cats, all so-called 'cutaneous reaction patterns' may be due to adverse food reactions. The most common gastrointestinal signs in both species are diarrhoea and vomiting. An elimination diet over several weeks using a protein source and a carbohydrate source previously not fed is still the diagnostic tool of choice. Improvement on such a diet, deterioration on re-challenge with the old food and improvement again on the elimination diet confirms the diagnosis of adverse food reaction, whereas alternative tests of blood, serum, saliva and hair have been found to be unsatisfactory. Patch testing with food antigens has been recommended as an aid to choose the elimination diet ingredients, since it has a reasonable negative predictability and likelihood ratio, but is laborious and costly.